Method for preparing composite thermal insulation material by recycling and reusing environment-friendly waste aluminum silicate product
By recycling the waste aluminum silicate products into spherical composite particles and coated aluminum silicate products, and adding them to epoxy resin-based coatings, composite insulation materials with excellent mechanical properties and thermal insulation properties are prepared, and the problem that the coating mechanical properties and thermal insulation properties in the prior art cannot be combined.
Patent Information
- Application Number
- CN202411848312.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, waste aluminum silicate products with low thermal conductivity are added to the coating, and there is a problem that the coating cannot have both mechanical properties and thermal insulation properties.
By recycling waste aluminum silicate products in the form of spherical composite particles and coated aluminum silicate products, and adding them to epoxy resin-based coatings, combined with the use of modified chain extenders and organic solvents, composite insulation materials with excellent mechanical properties and insulation properties are prepared.
It realizes the balance between the mechanical properties and insulation properties of composite insulation materials, improves the thermal insulation performance of coatings, and solves the resource recycling and environmental pollution problems of waste aluminum silicate products.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation materials, and in particular to a method for preparing a composite thermal insulation material by recycling and reusing environmentally friendly waste aluminum silicate products. Background Art
[0002] As inorganic fiber materials, aluminum silicate products mainly include aluminum silicate plates, aluminum silicate blankets, aluminum silicate felts, aluminum silicate shells, aluminum silicate ceramic fibers, etc. High-temperature pipelines, equipment and heating furnace linings of petrochemical enterprises mostly use aluminum silicate wool and its products as thermal insulation materials. Every time the equipment and pipelines are inspected, repaired and dismantled, a large amount of thermal insulation materials will be replaced. At present, the treatment of waste aluminum silicate products represented by waste aluminum silicate wool is relatively extensive, which will lead to waste of resources and environmental pollution. If the above-mentioned waste aluminum silicate products can be recycled and reused, good economic and social benefits will be achieved.
[0003] As a typical engineering industry, the construction industry accounts for more than 40% of the total social energy consumption, the largest proportion. Reducing energy consumption during the use of buildings is the key to reducing building energy consumption. The factors that affect the energy consumption of buildings are mainly the thermal insulation performance of buildings. Selecting suitable thermal insulation coatings for exterior wall materials is an effective way to reduce building energy loss. Aluminum silicate has a low thermal conductivity. If recycled waste aluminum silicate products can be added to the prepared thermal insulation coating, it can not only achieve the recycling and reuse of waste aluminum silicate products, but also help improve the thermal insulation performance of the coating.
[0004] Patent application CN104087077A discloses a phase change heat storage and thermal insulation coating based on phase change heat storage, and its preparation method and application. Paraffin is wrapped with silicon dioxide, and titanium dioxide is deposited on the surface to obtain a phase change microcapsule with a composite structure, which has good mechanical properties and thermal insulation properties. If aluminum silicate can be coated with organic materials, the compatibility of aluminum silicate and coating and the thermal insulation performance of the coating can be improved.
[0005] Patent application CN109437812A discloses a thermal insulation coating and a preparation method thereof. Recycled waste aluminum silicate and aerogel are used as thinner components, mixed with quicklime and hollow vitrified microspheres to prepare a coating with good anti-corrosion and heat insulation effects. However, in the above coating, inorganic materials such as waste aluminum silicate and hollow vitrified microspheres are prone to agglomeration, and the mechanical properties of the thermal insulation coating after coating are poor.
[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a method for recycling and reusing environmentally friendly waste aluminum silicate products to prepare composite thermal insulation materials, which is used to solve the technical problem in the prior art that waste aluminum silicate products with low thermal conductivity are added to coatings, resulting in the coatings failing to have both mechanical properties and thermal insulation properties.
[0008] The purpose of the present invention can be achieved by the following technical solutions: A method for recycling and reusing environmentally friendly waste aluminum silicate products to prepare composite thermal insulation materials comprises the following steps: S1. According to parts by weight, 15-20 parts of spherical composite particles are added to 50 parts of organic solvent, and ultrasonic dispersion is performed to obtain a uniform suspension; 5-10 parts of coated aluminum silicate products, 50-60 parts of epoxy resin, 5-10 parts of modified chain extender and 5-8 parts of amine curing agent are added to the above suspension, mixed and stirred, and uniformly dispersed to obtain a mixture; S2. Pour the mixture into a mold and cure it at 60-70° C. for 24 hours to obtain a molded sample; demould the molded sample to obtain a composite thermal insulation material.
[0009] Waste aluminum silicate products are recovered in the form of spherical composite particles and coated aluminum silicate products, and a small amount of modified chain extender is added for modification, thereby preparing an epoxy resin-based coating, which is the composite thermal insulation material prepared by the present invention.
[0010] Furthermore, the method for preparing the coated aluminum silicate product comprises the following steps: A1. Screening the waste aluminum silicate wool to remove impurities; then washing, drying and grinding to obtain waste aluminum silicate powder; Waste aluminum silicate wool is used as the raw material for waste aluminum silicate products, and waste aluminum silicate powder is collected through primary screening and grinding processes.
[0011] A2, tetraallyl silicate and dimethylethoxysilane are mixed and placed in an ice-salt bath at 0-10°C; a platinum catalyst is then added, mixed and stirred to obtain a mixed solid-liquid; the mixed solid-liquid is placed in a closed environment and reacted at room temperature for 30-40 minutes to obtain a modified organosilicon; Under the action of platinum catalyst, the double bond in tetraallyl silicate can undergo addition reaction with the silicon-hydrogen bond in dimethylethoxysilane to obtain modified silicone.
[0012]
[0013] A3. Modified silicone, terminal hydroxyl polydimethylsiloxane, dibutyltin dilaurate and waste aluminum silicate powder are mixed and stirred to obtain a mixed raw material; the mixed raw material is then placed in a vacuum oven with negative pressure, and cured at room temperature for 24 hours to obtain a coated aluminum silicate product.
[0014] After the terminal hydroxyl polydimethylsiloxane is activated by the catalyst dibutyltin dilaurate, activated silanol groups can be obtained. The activated silanol groups can undergo dealcoholization condensation reaction with the siloxane groups of the modified silicone to obtain coated aluminum silicate products.
[0015] The reaction principle of modified silicone and terminal hydroxyl polydimethylsiloxane is as follows:
[0016] Furthermore, in step A1, the waste aluminum acid powder contains 40-45%wt of Al2O3, 50-51%wt of SiO2, 0.5%wt of Fe2O3, and the rest is other impurities; in step A2, the dosage ratio of tetraallyl silicate, dimethylethoxysilane and platinum catalyst is 25-35g:10-15g:1-3g; in step A3, the dosage ratio of modified silicone, terminal hydroxyl polydimethylsiloxane, dibutyltin dilaurate and waste aluminum silicate powder is 35-50g:40-60g:1-3g:30-40g.
[0017] Furthermore, the preparation method of the modified chain extender comprises the following steps: B1, adding ammonium polyphosphate and chitosan to an acidic aqueous solution, mixing and stirring until the solid is completely dissolved to obtain a mixed solution; B2. The mixed solution is reacted at 70-80° C. for 3-4 hours, and ammonia generated during the reaction is removed to obtain a reaction solution; the reaction solution is distilled to remove deionized water, and the solid is collected. The solid is washed with deionized water to neutrality, and then vacuum dried to constant weight to obtain a modified chain extender.
[0018] The ammonium radical of ammonium polyphosphate reacts with the amine group in chitosan to release ammonia gas, and the harvested solid is chitosan modified with ammonium polyphosphate, which is a modified chain extender.
[0019] The reaction principle of ammonium polyphosphate and chitosan is as follows:
[0020] Furthermore, in step B1, the usage ratio of ammonium polyphosphate, chitosan and acidic aqueous solution is 2-5g:5-10g:100mL; the acidic aqueous solution is a hydrochloric acid aqueous solution with a pH value of 3-4.
[0021] Furthermore, the method for preparing the spherical composite particles comprises the following steps: The waste aluminum silicate powder is finely ground to obtain ultrafine powder with an average particle size of 140-150nm; lead oxide with an average particle size of 40-50μm and the ultrafine powder are added into the particle compounding system according to parts by weight to obtain spherical composite particles.
[0022] Waste aluminum silicate powder is ground twice to obtain ultrafine powder with a particle size of 140-150nm as sub-particles, and then lead oxide with an average particle size of 40-50μm is used as mother particles. The two particles with a large particle size difference are physically and mechanically composited to obtain spherical composite particles.
[0023] Furthermore, in parts by weight, the weight ratio of lead oxide to waste aluminum silicate powder is 90-95:5-10; the rotation speed of the rotor of the composite system is 3000-5000 r / min, the system processing time is 5-15 min, and the feeding amount of the system each time is 200-500 g.
[0024] Furthermore, in step S1, the frequency of ultrasonic dispersion is 20-30kHZ, and the ultrasonic duration is 20-30min; the organic solvent is n-butanol and N-methyl-2-pyrrolidone mixed in a mass ratio of 2-3:1; the weight ratio of the suspension to the coated aluminum silicate product is 65-70:5-10; the epoxy resin is bisphenol A epoxy resin, and the curing agent is any one of diethylenetriamine, ethylenediamine or diethylenetriamine.
[0025] The present invention has the following beneficial effects: 1. The composite thermal insulation material prepared by the present invention is essentially an epoxy resin-based composite coating. n-Butanol and N-methyl-2-pyrrolidone are used as organic solvents, and the epoxy resin is cured to obtain a composite coating. Chitosan can react with bisphenol A type epoxy resin to improve the mechanical properties of the prepared composite thermal insulation material through chain extension; chitosan is pre-modified with ammonium polyphosphate to further improve its own flame retardant properties. Waste aluminum silicate wool containing high silicon and high aluminum elements is recycled to obtain waste aluminum silicate powder. Then, the waste aluminum silicate powder is used as a raw material to prepare aluminum silicate products coated with organic-inorganic composite materials and spherical composite particles, respectively, which can improve their own mechanical properties and thermal insulation properties.
[0026] 2. When preparing coated aluminum silicate products, tetraallyl silicate and dimethylethoxysilane undergo addition reaction to obtain modified organic silicon with short chain and network structure; terminal hydroxyl polydimethylsiloxane is used as long chain organic silicon; modified organic silicon and terminal hydroxyl polydimethylsiloxane react to form a long-short chain interpenetrating network structure. The above organic materials are compositely coated with waste aluminum silicate powder to block the heat conduction path of waste aluminum silicate, thereby improving its own thermal insulation performance.
[0027] 3. Grind the waste aluminum silicate powder for a second time to obtain ultrafine powder with a particle size of nanometer level as sub-particles, and select lead oxide with a particle size of micrometer level as mother particles; add the sub-particles and mother particles into the particle composite system, and utilize the large particle size difference between the sub-particles and the mother particles, the agglomeration of the nano-level sub-particles and the high-speed airflow generated by the system rotor, under the action of strong impact force, the sub-particles are firmly adhered to the mother particles in a short time to produce chemical bonding, thereby forming firm, spherical composite particles. The use of lead oxide with low thermal conductivity to coat the surface of the waste aluminum silicate powder not only improves the thermal insulation performance of the composite particles, but also effectively improves the dispersibility of lead oxide. The composite thermal insulation material prepared by the present invention has excellent mechanical properties and high thermal insulation performance. DETAILED DESCRIPTION
[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The platinum catalyst used in Examples 1-3 of the present invention was purchased from Heraeus Precious Metals Technology Co., Ltd., with activated carbon as the carrier, and the model is HS-100; the terminal hydroxyl polydimethylsiloxane used in Examples 1-3 of the present invention was purchased from Jinan Xinglongda Chemical Co., Ltd., with a CAS number of 70131-67-8 and a molecular weight of 300-500; the polyphosphoric acid used in Examples 4-6 of the present invention was purchased from McLean Reagent, with a CAS number of 68333-79-9, a product number of A875114, and a degree of polymerization n=10-20; the waste aluminum silicate powder used in Examples 7-9 is the waste aluminum silicate powder prepared in step A1 of Example 1; the lead oxide used in Examples 7-9 of the present invention was purchased from Hebei Chaoyue Wear Resistant Materials Co., Ltd., and the particle size was 40-50 μm.
[0030] Example 1 This embodiment provides an environmentally friendly method for recycling and reusing waste aluminum silicate products to prepare coated aluminum silicate products for composite thermal insulation materials, comprising the following steps: A1. Collect the waste aluminum silicate wool from the composite lining of the industrial kiln, and remove other solid waste impurities through preliminary screening; use deionized water to wash, filter and remove the moisture in the waste aluminum silicate wool, and then dry it to obtain the pretreated waste aluminum silicate products. Grind the pretreated waste aluminum silicate products to 120 mesh to obtain waste aluminum silicate powder. The above waste aluminum silicate powder contains 45%wt of Al2O3, 51%wt of SiO2, 0.5%wt of Fe2O3, and the rest is other impurities.
[0031] A2. Add 25g of tetraallyl silicate and 10g of dimethylethoxysilane to a 250mL beaker, then place the beaker in an ice-salt bath and set the temperature of the ice-salt bath to 0°C. Then add 1g of platinum catalyst to the beaker and stir at 500r / min for 30s to obtain a mixed solid-liquid. Transfer the mixed solid-liquid to a three-necked flask, seal it, and react at room temperature for 30min to obtain a gel-like modified silicone.
[0032] A3. Add 30g of modified silicone, 40g of terminal hydroxyl polydimethylsiloxane (molecular weight of 500), 1g of dibutyltin dilaurate and 30g of waste aluminum silicate powder into a 500mL three-necked flask, stir well for 10min at a stirring speed of 100r / min, mix well to obtain a mixed raw material; then put the three-necked flask into a vacuum oven with negative pressure, and cure at room temperature for 24h to obtain a coated aluminum silicate product.
[0033] Example 2 This embodiment provides an environmentally friendly method for recycling and reusing waste aluminum silicate products to prepare coated aluminum silicate products for composite thermal insulation materials, comprising the following steps: A1. Collect the waste aluminum silicate wool from the composite lining of the industrial kiln, and remove other solid waste impurities through preliminary screening; use deionized water to wash, filter and remove the moisture in the waste aluminum silicate wool, and then dry it to obtain the pretreated waste aluminum silicate products. Grind the pretreated waste aluminum silicate products to 100 mesh to obtain waste aluminum silicate powder. The above waste aluminum silicate powder contains 43.3%wt of Al2O3, 50.5%wt of SiO2, 0.51%wt of Fe2O3, and the rest is other impurities.
[0034] A2. Add 30g of tetraallyl silicate and 12g of dimethylethoxysilane to a 250mL beaker, then place the beaker in an ice-salt bath and set the temperature of the ice-salt bath to 5°C. Then add 2g of platinum catalyst to the beaker and stir at 550r / min for 30s to obtain a mixed solid-liquid. Transfer the mixed solid-liquid to a three-necked flask, seal it, and react at room temperature for 35min to obtain a gel-like modified silicone gel.
[0035] A3. Add 45g of modified silicone, 50g of terminal hydroxyl polydimethylsiloxane (molecular weight of 400), 2g of dibutyltin dilaurate and 35g of waste aluminum silicate powder into a 500mL three-necked flask, stir well for 10min at a stirring speed of 100r / min, mix well to obtain a mixed raw material; then put the three-necked flask into a vacuum oven with negative pressure, and cure at room temperature for 24h to obtain a coated aluminum silicate product.
[0036] Example 3 This embodiment provides an environmentally friendly method for recycling and reusing waste aluminum silicate products to prepare coated aluminum silicate for composite thermal insulation materials, comprising the following steps: A1. Collect the waste aluminum silicate wool from the composite lining of the industrial kiln, and remove other solid waste impurities through preliminary screening; use deionized water to wash, filter and remove the moisture in the waste aluminum silicate wool, and then dry it to obtain the pretreated waste aluminum silicate products. Grind the pretreated waste aluminum silicate products to 100 mesh to obtain waste aluminum silicate powder. The above waste aluminum silicate powder contains 40%wt of Al2O3, 50%wt of SiO2, 0.6%wt of Fe2O3, and the rest is other impurities.
[0037] A2. Add 35g of tetraallyl silicate and 15g of dimethylethoxysilane to a 250mL beaker, then place the beaker in an ice-salt bath and set the temperature of the ice-salt bath to 10°C. Then add 3g of platinum catalyst to the beaker and stir at 600r / min for 30s to obtain a mixed solid-liquid mixture. Transfer the mixed solid-liquid mixture to a three-necked flask, seal it, and react at room temperature for 40min to obtain a gel-like modified silicone.
[0038] A3. Add 50g of modified silicone, 60g of terminal hydroxyl polydimethylsiloxane (molecular weight of 300), 3g of dibutyltin dilaurate and 40g of waste aluminum silicate powder into a 500mL three-necked flask, stir well for 10min at a stirring speed of 200r / min, mix well to obtain a mixed raw material; then put the three-necked flask into a vacuum oven with negative pressure, and cure at room temperature for 24h to obtain a coated aluminum silicate product.
[0039] Example 4 This embodiment provides a method for preparing a modified chain extender for a composite thermal insulation material, comprising the following steps: B1. Add 10%wt hydrochloric acid solution to deionized water to adjust the pH value of deionized water to 3. Connect the three-necked flask to the air pipe and thermometer, then add 100mL of acidic aqueous solution, 2g of ammonium polyphosphate (n=10) and 5g of chitosan into the three-necked flask, mix and stir until the ammonium polyphosphate and chitosan are completely dissolved in the acidic aqueous solution to obtain a mixed solution.
[0040] B2. The three-necked flask was then transferred to a water bath and reacted at 70°C for 3 hours. During the reaction, the waste gas ammonia was collected through a gas guide tube to obtain a reaction solution. The reaction solution was distilled to remove deionized water and the solid was collected; the solid was washed with deionized water until the pH value was neutral, and then vacuum dried to constant weight to obtain a modified chain extender.
[0041] Example 5 This embodiment provides a method for preparing a modified chain extender for a composite thermal insulation material, comprising the following steps: B1. Add 10%wt hydrochloric acid solution to deionized water to adjust the pH value of deionized water to 4. Connect the air pipe and thermometer to the three-necked flask, then add 100mL of acidic aqueous solution, 3g of ammonium polyphosphate (n=15) and 8g of chitosan into the three-necked flask, mix and stir until the ammonium polyphosphate and chitosan are completely dissolved in the acidic aqueous solution.
[0042] B2. The three-necked flask was then transferred to a water bath and reacted at 75°C for 4 hours. During the reaction, the waste gas ammonia was collected through a gas guide tube to obtain a reaction solution. The reaction solution was distilled to remove deionized water and the solid was collected; the solid was washed with deionized water until the pH value was neutral, and then vacuum dried to constant weight to obtain a modified chain extender.
[0043] Example 6 This embodiment provides a method for preparing a modified chain extender for a composite thermal insulation material, comprising the following steps: B1. Add 10%wt hydrochloric acid solution to deionized water to adjust the pH value of deionized water to 4. Connect the three-necked flask to the air pipe and thermometer, then add 100mL of acidic aqueous solution, 5g of ammonium polyphosphate (n=20) and 10g of chitosan into the three-necked flask, mix and stir until the ammonium polyphosphate and chitosan are completely dissolved in the acidic aqueous solution to obtain a mixed solution.
[0044] B2. The three-necked flask was then transferred to a water bath and reacted at 80°C for 4 hours. During the reaction, the waste gas ammonia was collected through a gas guide tube to obtain a reaction solution. The reaction solution was distilled to remove deionized water and the solid was collected; the solid was washed with deionized water until the pH value was neutral, and then vacuum dried to constant weight to obtain a modified chain extender.
[0045] Example 7 This embodiment provides a method for preparing a composite thermal insulation material, comprising the following steps: S1. Add waste aluminum silicate powder into an ultrafine powder grinder, grind to obtain ultrafine powder with an average particle size of 140nm, and obtain waste aluminum silicate powder as sub-particles. Select lead oxide with an average particle size of 40μm as the mother particle. According to weight parts, 95 parts of lead oxide and 5 parts of waste aluminum silicate powder are added to the particle composite system, the rotor speed of the above system is 3000r / min, the system processing time is 15min, and the feeding amount is 500g each time to obtain spherical composite particles.
[0046] S2, n-butanol and N-methyl-2-pyrrolidone were mixed uniformly in a mass ratio of 2:1 to obtain an organic solvent. 15 parts of the spherical composite particles were added to 50 parts of the organic solvent by weight, and ultrasonicated at 30 kHz for 20 minutes at room temperature to uniformly disperse the spherical composite particles in the organic solvent to obtain a uniformly mixed suspension.
[0047] S3. Add 5 parts of the coated aluminosilicate prepared in Example 3, 50 parts of bisphenol A epoxy resin, 5 parts of the modified chain extender prepared in Example 6 and 5 parts of diethylenetriamine curing agent to 65 parts of the suspension in order by weight, mix and stir at 100 r / min for 1 hour to make it uniformly dispersed to obtain a mixture.
[0048] S4. The mixture is placed in a high temperature oven and cured at 60° C. for 24 hours to obtain a composite thermal insulation material.
[0049] Example 8 This embodiment provides a method for preparing a composite thermal insulation material, comprising the following steps: S1. Add waste aluminum silicate powder into an ultrafine powder grinder, grind to obtain ultrafine powder with an average particle size of 141nm, and obtain waste aluminum silicate powder as mother particles. Select lead oxide with an average particle size of 45μm as daughter particles. According to weight parts, 92 parts of lead oxide and 6 parts of waste aluminum silicate powder are added to the particle composite system, the rotor speed of the above system is 4000r / min, the system processing time is 10min, and the feeding amount is 300g each time to obtain spherical composite particles.
[0050] S2, n-butanol and N-methyl-2-pyrrolidone were mixed uniformly in a mass ratio of 3:1 to obtain an organic solvent. 18 parts of the spherical composite particles were added to 50 parts of the organic solvent by weight, and ultrasonicated at 20 kHz for 30 minutes at room temperature to uniformly disperse the spherical composite particles in the organic solvent to obtain a uniformly mixed suspension.
[0051] S3. In parts by weight, add 6 parts of the coated aluminosilicate prepared in Example 3, 55 parts of bisphenol A epoxy resin, 6 parts of the modified chain extender prepared in Example 6 and 6 parts of diethylenetriamine curing agent to 68 parts of the suspension in sequence, and stir at 150 r / min for 1.5 hours to make it uniformly dispersed to obtain a mixture.
[0052] S4. The mixture is placed in a high temperature oven and cured at 62° C. for 24 hours to obtain a composite thermal insulation material.
[0053] Example 9 This embodiment provides a method for preparing a composite thermal insulation material, comprising the following steps: S1. Add waste aluminum silicate into an ultrafine powder grinder and grind to obtain ultrafine powder with an average particle size of 150nm, and obtain waste aluminum silicate powder as the mother particle. Select lead oxide with an average particle size of 50μm as the daughter particle. According to weight parts, 90 parts of lead oxide and 10 parts of waste aluminum silicate powder are added to the particle composite system, the rotor speed of the above system is 5000r / min, the system processing time is 15min, and the feeding amount is 200g each time to obtain spherical composite particles.
[0054] S2, n-butanol and N-methyl-2-pyrrolidone were mixed uniformly in a mass ratio of 3:1 to obtain an organic solvent. 20 parts of the spherical composite particles were added to 50 parts of the organic solvent by weight, and ultrasonicated at 20 kHz for 30 minutes at room temperature to uniformly disperse the spherical composite particles in the organic solvent to obtain a uniformly mixed suspension.
[0055] S3. In parts by weight, add 10 parts of the coated aluminosilicate prepared in Example 3, 60 parts of bisphenol A epoxy resin, 10 parts of the modified chain extender prepared in Example 6 and 8 parts of diethylenetriamine curing agent to 70 parts of the suspension in sequence, and stir at 200 r / min for 2 hours to make it uniformly dispersed to obtain a mixture.
[0056] S4. The mixture is placed in a high temperature oven and cured at 70° C. for 24 hours to obtain a composite thermal insulation material.
[0057] Comparative Example 1 Compared with the composite thermal insulation material prepared in Example 7, the present invention eliminates step A2 when preparing the coated aluminum silicate product, and replaces the modified silicone with tetraallyl silicate of equal mass.
[0058] Comparative Example 2 Compared with the composite thermal insulation material prepared in Example 7, when preparing the coated aluminum silicate product, the present invention eliminates step A2 and replaces the modified silicone with dimethylethoxysilane of the same mass.
[0059] Comparative Example 3 Compared with the composite thermal insulation material prepared in Example 7, the present invention uses chitosan of equal mass as a substitute chain extender when preparing the modified chain extender.
[0060] Comparative Example 4 Compared with the composite thermal insulation material prepared in Example 7, the lead oxide is ground to an average particle size of 140 nm when preparing the spherical composite particles.
[0061] Performance Testing: According to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", the composite thermal insulation materials prepared in Examples 7-9 and Comparative Examples 1-4 were stretched using an electronic universal testing machine at a stretching rate of 10 mm / min, and their elongation at break was measured. Each sample was measured three times in parallel to obtain an average value. 2. According to GB / T531.1-2008 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber", the hardness of the composite thermal insulation materials prepared in Examples 7-9 and Comparative Examples 1-4 was tested. The load size was 1 kgf and the load holding time was 10 s. Five points were taken for each sample for testing, and the results were averaged.
[0062] 3. According to GB / T2406-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method", the composite thermal insulation materials prepared in Examples 7-9 and Comparative Examples 1-4 were subjected to limiting oxygen index tests.
[0063] 4. According to ISO22007-2 "Heat Conductivity Standards and Test Methods", the thermal conductivity of the composite insulation materials prepared in Examples 7-9 and Comparative Examples 1-4 was tested using a thermal constant analyzer, and the thermal conductivity values were recorded.
[0064] 5. The composite thermal insulation materials prepared in Examples 7-9 and Comparative Examples 1-4 were placed on a heating table in turn, and the hot and cold surface temperatures were collected using a K-type thermocouple. The temperature data was recorded using a data acquisition device. A butane burner was used to heat the thermal insulation coating to a higher temperature, and an infrared thermal imager was used to record the hot and cold surface temperatures of the thermal insulation coating, and the thermal insulation temperature difference value was recorded. The specific test results are shown in the table below: Table 1. Sample performance test data
[0065] Data analysis: By comparing and analyzing the data in Table 1, the composite thermal insulation materials prepared by Examples 7-9 of the present invention and Comparative Examples 1-3 all have excellent mechanical properties, which are manifested in that the elongation at break and hardness values of the prepared composite thermal insulation materials are relatively high; the added organic-inorganic composite material (coated aluminum silicate products and spherical composite particles) has high compatibility with the composite thermal insulation material, which can improve the mechanical properties of the composite thermal insulation material and alleviate the technical problems of agglomeration and poor dispersibility of inorganic-based materials. However, in Comparative Example 4, both the mother particles and the daughter particles are ground to the nanometer level. Although the nanometer-level powder has a stronger agglomeration ability than the micrometer-level powder, the mother particles and the daughter particles lose the corresponding particle size difference, which is manifested in that the firmness of the prepared spherical composite particles is reduced, and the mechanical properties (elongation at break and hardness value) of the composite thermal insulation material prepared in Comparative Example 4 are significantly reduced.
[0066] In Comparative Example 1, tetraallyl silicate was used to replace modified organosilicon; in Comparative Example 2, dimethylethoxysilane was used to replace modified organosilicon. The coated aluminum silicate products prepared in Comparative Example 1 and Comparative Example 2 did not form an interpenetrating network structure of organosilicon with multiple short-chain branches and long-chain structures, thereby weakening the coating performance of aluminum silicate and increasing the thermal conduction path of waste aluminum silicate, which was manifested in an increase in the thermal conductivity value of the prepared waste aluminum silicate products and a decrease in the thermal insulation temperature difference value.
[0067] In Comparative Example 3, chitosan of equal mass was used to replace the modified chain extender, and the addition of chitosan helped to increase the mechanical properties of the prepared composite thermal insulation material. However, compared with chitosan, the modified chain extender not only has the same mechanical properties (shown as similar elongation at break and hardness), but also has excellent flame retardant properties, shown as a lower limiting oxygen index value.
[0068] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0069] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0070] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for recycling and reusing environmentally friendly waste aluminum silicate products to prepare composite thermal insulation materials, characterized in that: The following steps are involved: S1. According to parts by weight, 15-20 parts of spherical composite particles are added to 50 parts of organic solvent, and ultrasonic dispersion is performed to obtain a uniform suspension; 5-10 parts of coated aluminum silicate products, 50-60 parts of epoxy resin, 5-10 parts of modified chain extender and 5-8 parts of curing agent are added to the suspension, mixed and stirred, and uniformly dispersed to obtain a mixture; S2. The mixture is cured at 60-70° C. for 24 hours to obtain a composite thermal insulation material.
2. The method for preparing composite thermal insulation materials by recycling and reusing environmentally friendly waste aluminum silicate products according to claim 1, characterized in that: The method for preparing the coated aluminum silicate product comprises the following steps: A1. Screening the waste aluminum silicate wool to remove impurities; then washing, drying and grinding to obtain waste aluminum silicate powder; A2, tetraallyl silicate and dimethylethoxysilane are mixed and placed in an ice-salt bath at 0-10°C; a platinum catalyst is then added, mixed and stirred to obtain a mixed solid-liquid; the mixed solid-liquid is placed in a closed environment and reacted at room temperature for 30-40 minutes to obtain a modified organosilicon; A3. Modified silicone, terminal hydroxyl polydimethylsiloxane, dibutyltin dilaurate and waste aluminum silicate powder are mixed and stirred to obtain a mixed raw material; the mixed raw material is then placed in a vacuum oven with negative pressure, and cured at room temperature for 24 hours to obtain a coated aluminum silicate product.
3. The method for preparing composite thermal insulation materials by recycling and reusing environmentally friendly waste aluminum silicate products according to claim 1, characterized in that: In step A1, the waste aluminum silicate powder contains 40-45%wt of Al2O3, 50-51%wt of SiO2, 0.5%wt of Fe2O3, and the rest is other impurities; in step A2, the amount ratio of tetraallyl silicate, dimethylethoxysilane and platinum catalyst is 25-35g:10-15g:1-3g; in step A3, the amount ratio of modified silicone, terminal hydroxyl polydimethylsiloxane, dibutyltin dilaurate and waste aluminum silicate powder is 35-50g:40-60g:1-3g:30-40g.
4. The method for preparing composite thermal insulation materials by recycling and reusing environmentally friendly waste aluminum silicate products according to claim 1, characterized in that: The preparation method of the modified chain extender comprises the following steps: B1, adding ammonium polyphosphate and chitosan to an acidic aqueous solution, mixing and stirring until the solid is completely dissolved to obtain a mixed solution; B2. The mixed solution is reacted at 70-80° C. for 3-4 hours, and ammonia generated during the reaction is removed to obtain a reaction solution; the reaction solution is distilled to remove deionized water, and the solid is collected. The solid is washed with deionized water to neutrality, and then vacuum dried to constant weight to obtain a modified chain extender.
5. The method for preparing composite thermal insulation materials by recycling and reusing environmentally friendly waste aluminum silicate products according to claim 4, characterized in that: In step B1, the usage ratio of ammonium polyphosphate, chitosan and acidic aqueous solution is 2-5g:5-10g:100mL; the acidic aqueous solution is a hydrochloric acid aqueous solution with a pH value of 3-4.
6. The method for preparing composite thermal insulation materials by recycling and reusing environmentally friendly waste aluminum silicate products according to claim 1, characterized in that: The preparation method of the spherical composite particles comprises the following steps: The waste aluminum silicate powder is finely ground to obtain ultrafine powder with an average particle size of 140-150nm; lead oxide with an average particle size of 40-50μm and the ultrafine powder are added into the particle compounding system to obtain spherical composite particles.
7. The method for preparing composite thermal insulation materials by recycling and reusing environmentally friendly waste aluminum silicate products according to claim 6, characterized in that: The weight ratio of lead oxide to ultrafine powder is 90-95:5-10; the rotation speed of the rotor of the composite system is 3000-5000r / min, the system processing time is 5-15min, and the feeding amount of the system each time is 200-500g.
8. The method for preparing composite thermal insulation materials by recycling and reusing environmentally friendly waste aluminum silicate products according to claim 1, characterized in that: In step S1, the frequency of ultrasonic dispersion is 20-30kHZ, and the ultrasonic duration is 20-30min; the organic solvent is n-butanol and N-methyl-2-pyrrolidone mixed in a mass ratio of 2-3:1; the weight ratio of the suspension to the coated aluminum silicate product is 65-70:5-10; the epoxy resin is bisphenol A epoxy resin, and the curing agent is any one of diethylenetriamine, ethylenediamine or diethylenetriamine.
Citation Information
Patent Citations
Phase-change heat storage insulation coating based on phase-change heat storage as well as preparation method and application of coating
CN104087077A
Thermal insulation coating and preparation method thereof
CN109437812A
Cited By
Preparation method of composite epoxy resin material
CN120944293A